Pola Komunikasi Efektif Dalam Mengatasi Masalah Belajar: (Studi Deskriptif Kualitatif Tentang Kegiatan Mengatasi Masalah Belajar Yang Dialami Peserta Didik Pada Proses Belajar di SMA Muhammadiyah 2 Ngawi) - Wibawati Bermi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2016)
This research is about activities in overcoming learning problems through the learners for learning process in the school. The school is SMA Muhammadiyah 2Ngawi. This research is focused on qualitative descriptive research. This study uses interpretive perspective in interpreting the phenomenon approached. In a While the data analysis instrument, researcher uses descriptive data analysis techniques. In this study, researcher tries to examine how the pattern of effective communication in overcoming learning problems through the learners for learning process is. The subjects of the study are the teachers included teachers of National Final Exam’s class and Teachers of counseling who specifically related to activities of learning problem solving. Based on the formulation of the problem is: